2020
DOI: 10.21037/atm-20-7391
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of MRI in the diagnosis of anterior cruciate ligament injury

Abstract: Background: Anterior cruciate ligament (ACL) injury can cause damage to the meniscus and articular cartilage, and may even lead to osteoarthritis. This study aimed to analyze the accuracy and feasibility of magnetic resonance imaging (MRI) imaging signs in the diagnosis of knee joint ACL injury.Methods: A total of 78 patients admitted to our hospital from June 2018 to October 2019 with highly suspected ACL injury were selected for this prospective study. We used MRI and arthroscopy to diagnose the ACL injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…It showed that the MRI images under the reconstruction algorithm can effectively improve the diagnosis effect of knee joint epiphyseal injury. Zhao et al (2020) [29] mentioned the high resolution of MRI in the study, which can clearly show the damage of the meniscus and ligament of the patient and can classify the damage. is was consistent with the opinion of this article on the MRI results of meniscal injury patients, that is, MRI can clearly diagnose the surrounding soft tissue injury, showing soft tissue swelling, soft tissue gaps are blurred, and the soft tissue was patchy with low T1WI and high FS-PDWI signals.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that the MRI images under the reconstruction algorithm can effectively improve the diagnosis effect of knee joint epiphyseal injury. Zhao et al (2020) [29] mentioned the high resolution of MRI in the study, which can clearly show the damage of the meniscus and ligament of the patient and can classify the damage. is was consistent with the opinion of this article on the MRI results of meniscal injury patients, that is, MRI can clearly diagnose the surrounding soft tissue injury, showing soft tissue swelling, soft tissue gaps are blurred, and the soft tissue was patchy with low T1WI and high FS-PDWI signals.…”
Section: Discussionmentioning
confidence: 99%
“…This has prompted increasing attention toward the SB technique and the anatomical structure of the ACL. Knee magnetic resonance imaging (MRI) can re ect the basic physiological information of the ACL well 11 , and thus contralateral knee joint MRI examinations have become an important part of personalized ACL reconstructions. MRI analysis of normal knee joints has shown its capability to provide an anatomical basis for the ACL reconstruction procedure, including ACL size and insertion area, the positional relationship with the surrounding anatomical landmarks with different motions, and the size requirement of the autograft.…”
Section: Introductionmentioning
confidence: 99%
“… 5–7 In a study conducted by Zhao et al, 78 participants were investigated; the diagnostic sensitivity, specificity, and accuracy of MRI for ACL injury were 95.45%, 91.67%, and 94.87%. 5 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 The typical MRI findings of ACL rupture include abnormal orientation and abnormal signal intensity of ACL. [5][6][7] In a study conducted by Zhao et al, 78 participants were investigated; the diagnostic sensitivity, specificity, and accuracy of MRI for ACL injury were 95.45%, 91.67%, and 94.87%. 5 Although MRI has high sensitivity and specificity, the diagnosis rate at the early stage of ACL rupture remains poor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation